Implementation of ASN Competency Development Policy in the Field of Procurement and Information Systems : Challenges and Solutions in Southwest Papua - Alfonsina Djitmau; Dian Ferriswara; Sapto Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The competency development of the State Civil Apparatus (ASN: Aparatur Sipil Negara) is a key element in strengthening efficient, transparent, and accountable governance, especially in strategic sectors such as the procurement of goods/services and information systems. This study aims to analyze the implementation of ASN competency development policies in this field in Southwest Papua Province, as well as identify challenges and formulate adaptive solutions that are in accordance with local conditions. This study uses a qualitative descriptive approach with data collection techniques through observation and documentation in a number of agencies from the Bureau of Procurement of Goods and Services, the Communication and Information Service, the Regional Civil Service Agency, and several other related SKPDs. The data were analyzed using thematic analysis techniques to improve the validity of the findings. The results of the study show that the implementation of ASN competency development policies still faces obstacles in the form of limited understanding of regulations, low technical capabilities in the procurement and management of information systems, limitations of digital infrastructure, and a manual bureaucratic culture that is still dominant. The conclusion of this study emphasizes the importance of a competency development approach based on positional and contextual needs, with the support of adaptive regulations, continuous mentoring, and adequate digital infrastructure investment. This research contributes to the development of public administration science, especially in the formulation of ASN development policy implementation strategies that are more responsive to the challenges of disadvantaged regions and support the transformation of digital bureaucracy at the local level.